A CONTENT ANALYSIS OF â€œMALAYSIAN-LAHAD DATUâ€ CRISIS AND CRISIS RESPONSES IN ETHNIC NEWSPAPERS IN MALAYSIA - Manimegalai Ambikapathy; Hasmah Zanuddin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This research was to examine the portrayal of crisis response strategies in Malaysian local vernacular printed dailies in covering terrorism crises which is the Lahad Datu crisis in Malaysia. The researcher relied on Situational Crisis Communication Theory (SCCT) and Framing theory to identify the news coverage and appropriate solutions through newspaper framing. Five variables were identified by the researcher in examining crisis response strategies such as news category, news slants, news framing, news sources and portrayal of visuals. Through quantitative content analysis, data revealed that solution category was portrayed by Nanban daily but Sin Chew focused on the problem category. For the news slants, Sin Chew daily framed negative slants of news most but Nanban daily portrayed issues in positive slants. In measuring the news frame, both dailies focused more on the attribution of responsibility frame. In examining the crisis response strategies, the researcher found, justification crisis response was portrayed predominantly but there is a significant difference between two different vernacular dailies in the portrayal of justification crisis response followed by concern crisis response. Kruskal Wallisâ€™s test revealed that there is a significant difference in the portrayal of concern response between two dailies however, both newspapers having significant associations in portraying compensation crisis response.